Examining Malaysian young adults' motivation on the consumption of Instagram reels - Ong, Wing En (2024)
Instagram Reels are concise content videos that are measured in seconds rather than minutes. Nowadays, fewer people are watching TV or going to the movies. Yet they still want to be entertained. Thus, reels are a perfect source of entertainment for the younger generation of Instagram users. The issues that this investigation will attempt to solve are the limitation of demographic data as well as a lack of interaction engagement of young adults via Instagram in Malaysia regarding their motivation to consume. This study aims to investigate the demographic information of Malaysian Young Adults who consume Instagram Reels. It also wants to examine the motivation of young adults and their satisfaction with consuming Instagram Reels. A quantitative research approach is implemented in this analysis. Online questionnaires in the format of Google Forms will be distributed to 60 respondents. Then SPSS is used to analyse the survey data in this study. The present research holds importance in augmenting and deepening the analyses of Instagram usage in Malaysia so that researchers will gain a deeper and more comprehensive understanding of the motives of Instagram Reel users. The findings show that the variables, socially rewarding self-promotion, trendiness, and escape having a positive relationship with satisfaction of the consumption of Instagram Reels.